Teaching of arts and training of teachers and teachers in the recôncavo da Bahia (Palíndromo, 2022)
The text presents data from an ongoing research on art education and the training of art teachers in the Bahian Recôncavo. In line with the research done by the Teacher Training Observatory in the context of Art Education (OFPEA/BRARG) and identified gaps in the perspective of art education and teacher training for emancipation. The data presented comes from the research project entitled “Training Visual Arts Teachers in the Recôncavo Baiano: Expanding Limits in the Light of Historical-Critical Pedagogy” started in 2018, registered at the Center for Arts, Humanities and Letters of the Federal University of Reconcavo da Bahia. Without funding, the research is developed with the voluntary adherence of students from the degree course in visual arts. Two data collection instruments called “school diagnosis” and “theoretical and methodological practices of art teaching” were used. In this first data analysis approach, we have art teaching diluted in artistic activities, the use of art activities as a methodological strategy for learning other components. It was also registered the absence of teachers trained in the arts, insufficient workload and/or absent in the teaching stages of basic education. The urgency of a radical transformation in the teaching of art in Bahia’s Recôncavo and the expansion of the dialogue with popular culture is pointed out.
Keywords: Teacher training; Art education; Emancipation; Reconcavo Bahia